Analisis Keserasian Belanja Daerah Kabupaten Garut - Abdal, Abdal; Herabudin, Herabudin; Saodah, Siti (Publica: Jurnal Pemikiran Administrasi Negara, 2018)
The problem in this study relates to the level of compatibility of operating expenditures, capital expenditures as well as direct and indirect expenditure in the Budget Realization Report (LRA) Garut district fiscal year 2013-2017. The aim of this study was to determine the level of compatibility of operating expenditures, capital expenditures, as well as direct and indirect expenditure on Budget Realization Report (BRR) Garut regency Fiscal Year 2013-2017. The method used in this research is descriptive method with qualitative approach. Data collection techniques in this study is the observation, documentation, interviews and triangulation. Data analysis techniques in this study is an analysis model of Miles and Huberman which consists of three stages: 1) Reduction of data, 2) data, and 3) conclusion / verification. The result is the expenditures to Garut regency 2013-2017 fiscal year quite well.